ANALISIS PENGARUH GCG, LEVERAGE, DAN CSR TERHADAP PERFORMANCE FINANCIAL PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2018-2022 - Mufida Faridah; Endang Kartini; Sofiati Wardah (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2023)
This study aims to determine the effect of Good Corporate Governance which is proxied by (institutional ownership, audit committee, and board of directors), Leverage, and Corporate Social Responsibility on Financial Performance. The population of this study is 47 banking companies listed on the Indonesia Stock Exchange for the 2018-2022 period. Samples were taken using purposive sampling technique. Total samples taken were 26 companies. The data analysis technique used is multiple linear regression analysis. The test results show that institutional ownership with a significance of 0.587 > 0.05, audit committee with a significance of 0.500 > 0.05, board of directors with a significance of 0.552 > 0.05, and CSR with a significance of 0.218 > 0.05 has no significant effect on financial performance. Leverage with a significance value of 0.000 <0.05 has a negative and significant effect on financial performance.